ECONOMIC FREEDOM THE CZECH REPUBLIC AND ITS NEIGHBORS - Lubos Marek; Michal Vrabec (European Scientific Journal, ESJ, 2014)
We analyze the Index of Economic Freedom in Czech Republic in our article. The Index of Economic Freedom is an indicator which defines and tries to measure the economic freedom of a country or a region. The most famous are the Index of Economic Freedom created by the Heritage Foundation and the Wall Street Journal and Economic Freedom of the World published by the Canadian Fraser Institute. To analyze the Czech Republic‘s position it is reasonable to take into account its neighbors and Visegrad Four as the closest group. It is also insightful to compare it with other countries from the European Union (EU). According to Economic Freedom summary rating in 2011 all these countries belong to the ―Top 60‖: Germany (19), Austria and Hungary share 27 place (before Sweden), the Slovak Republic (36), the Czech Republic (52) and Poland (59). However, remembering the fact that there were significant changes during the last 25 years, it would be very interesting to look back to previous years.